1999
DOI: 10.1046/j.1365-2559.1999.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of laminin‐5 in the epithelium–stroma interface: an immunohistochemical marker of malignancy in epithelial lesions of the breast

Abstract: As recently described, the malignant transformation of breast epithelium with expression of an invasive phenotype is associated with a decrease of hemidesmosomes. The reduced immunostaining of laminin-5 is in line with this finding because laminin-5 represents the major component of the anchoring filaments attaching hemidesmosomes to the basement membrane. We feel that immunohistochemical demonstration of laminin-5 may serve as a marker of benignity in epithelial breast lesions. While other carcinoma types exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…Supporting our findings, loss of laminin 5 expression is also observed in invasive breast carcinomas and dedifferentiated mammary carcinoma cells (Henning et al, 1999;Miller et al, 2001). Our results suggest that altered expression and activation of laminin receptors like a6b4 during migration and local invasion of epithelial tumor cells (Rabinovitz and Mercurio, 1997;O'Connor et al, 1998) might not apply for dedifferentiated 'mesenchymal' cells after EMT.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Supporting our findings, loss of laminin 5 expression is also observed in invasive breast carcinomas and dedifferentiated mammary carcinoma cells (Henning et al, 1999;Miller et al, 2001). Our results suggest that altered expression and activation of laminin receptors like a6b4 during migration and local invasion of epithelial tumor cells (Rabinovitz and Mercurio, 1997;O'Connor et al, 1998) might not apply for dedifferentiated 'mesenchymal' cells after EMT.…”
Section: Introductionsupporting
confidence: 86%
“…In line with this, laminin 5 expression was lost in invasive, dedifferentiated breast carcinomas (Henning et al, 1999) and dedifferentiated, E-cadherin-negative breast carcinoma cells (MDA-MB-231; Miller et al, 2001). We thus assume that EMT abolishes formation or function of this integrin, which in polarized epithelial cells is restricted to cell-cell and cell-basement membrane contact areas and can be mobilized and activated during migration and local invasion of epithelial carcinoma cells after loss of polarity (O'Connor et al, 1998;Rabinovitz and Mercurio, 1997).…”
Section: Discussionsupporting
confidence: 60%
“…According to Henning et al (1999), the IHC demonstration of laminin-332 may serve as a marker of benignity in epithelial breast lesions. Fujita et al (2005) observed that chains of laminin-332 were expressed in the ductal epithelium basement membranes of the breast and diminished with tumor progression.…”
Section: Statisticalmentioning
confidence: 99%
“…They are believed to promote invasion of colon, breast, and skin cancer cells (Tsuruta et al, 2008). Along with clinical and pathological information, it has been used to assess tumor invasiveness (Hao et al, 1996;Henning et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Laminin-5, which consists of a3, b3, and c2 chains, is localized in epithelial basement membranes, functions as a ligand for integrins, and plays an important role in cell migration and adhesion [15,16]. Some studies have reported that laminin c2 is expressed at the invasive front in tumor cells, while others demonstrated that loss of laminin c2 in the epithelium-stroma interface is an immunohistochemical marker of malignancy in epithelial lesions [17][18][19][20][21]. Laminin c2 expression patterns are divided into two distinct types, cytoplasmic staining and extracellular staining.…”
Section: Introductionmentioning
confidence: 99%